A Paradigm Shift in Indian and International Patent Regime- Critical Review on Ex- and Current Scenario (Covid-19 Impact) (Journal of Intellectual Property Rights (JIPR), 2023)
The innovation markers are namely patents which give the creation the identity, novelty and utilization in industry or for commercial use in public. There were many patents filed under different judicatory laws of different countries which give the sole right and responsibility to own the invention till the expiry of patent by the owner(Patentee). The rules and regulations also enable the patentee to take necessary action against the misuse or prior use and also copying of invention. There are circumstances like national emergency like the Covid -19 pandemic which could create the urgency to make public access for the medicines under the clinical trial or the generic form before the expiry of the patent in order to increase the health care needs. The national emergency globally has awaken to recreate or amend few judiciary laws of different countries like waiver of patents, compulsory licenses and also paying a remuneration amount to the patentee. The countries like U.S, India, China, Japan have played a key role in managing the pandemic by encouraging generic medicine manufacturing and licensing. The COVID-19 crisis affects not only patent law. However, COVID-19 clearly presents an imminent threat to public health which, in most jurisdictions, is likely to justify the grant of compulsory licenses and more changes in the few penal codes and articles under specific provisions made by the government. There was also huge impact on the patent filings by different countries which enumerated the increase of 16 % by china and also a significant contribution by the countries like U.S, India, Europe, Japan, Italy etc. The Data exclusivity was reported including the women investors share which is considerably high. The pandemic has shaped new reforms in digitalization aspects and kept open many avenues in the medical and technology sectors in the years to come.